Evaluation of Electronic Prescribing Systems (EPS) Acceptance among Doctors and Pharmacists at UNS Hospital using the Technology Acceptance Model (TAM) - Joko Sudarsono; Satibi Satibi; Lutfan Lazuardi; Anna Wahyuni Widayanti (Journal of Health and Nutrition Research, 2026)
Implementing electronic prescribing systems (EPS) in hospitals is a complex process that extends beyond technological integration. It necessitates a comprehensive approach that considers the human factors involved, particularly the acceptance and willingness of healthcare professionals to adopt and utilize these systems effectively. This study aimed to evaluate the perceptions of doctors and pharmacists regarding the implementation of EPS at UNS Hospital using the Technology Acceptance Model (TAM). A validated questionnaire was administered to 50 respondents in UNS Hospital, assessing perceived ease of use, benefits, attitude towards usage, intention to use, and external factors. Most respondents (80%) agreed or strongly agreed that the system was easy to use. Furthermore, 90% acknowledged the benefits of EPS, including time savings, increased efficiency, accuracy, safety, and improved interprofessional communication. Attitudes towards usage were highly positive, with 92% of respondents expressing enthusiasm and comfort in transitioning to the electronic system. Intention to use was also high, with 86% committed to long-term adoption. However, external factors showed more varied results, with 66% agreeing or strongly agreeing, while 26% were doubtful and 8% disagreed, suggesting potential shortcomings in training, infrastructure, or technical assistance. These findings highlight the importance of addressing external factors to ensure the sustainability of EPS implementation Overall, the study indicates that the UNS Hospital EPS has the potential for widespread adoption and integration into healthcare services, given the positive perceptions of its ease of use, benefits, and user acceptance